The genus Notophthiracarus of New Zealand (Acari: Oribatida: Phthiracaridae): three new species and a key to 24 described species - Liu, Dong; Zhang, Zhi-Qiang (Zootaxa, 2013)
The genus Notophthiracarus (Acari: Oribatida: Phthiracaridae) was represented in New Zealand by 21 species prior to this work. In this paper, three new species of Notophthiracarus from New Zealand are described: Notophthiracarus dugdalei sp. nov. and Notophthiracarus matatatipu sp. nov. from Darran Mts., Tutoko Bench, and Notophthiracarus whakau sp. nov. from the Red Island, Mercury Islands. A key to all known species of Notophthiracarus in New Zealand is also provided.